The effects of intra-articular levobupivacain versus levobupivacain plus magnesium sulfate on postoperative analgesia in patients undergoing arthroscopic meniscectomy: A prospective randomized controlled study - Nurcan Kızılcık; Turhan Özler; Ferdi Menda; Çağatay Uluçay; Özge Köner; Faik Altıntaş (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to compared the effectiveness of intraarticular levobupivacain with levobupivacain and magnesium sulfate. Methods: In this prospective randomized double blinded study, 96 patients (67 male, 29 female; age range: 18–65 years) with ASA (American Society of Anesthesiologist) score I and II, who had undergone arthroscopic meniscectomy operation, were divided to 3 groups that had postoperative analgesia with intra-articular saline injection (control group), levobupivacain injection (L group) or levobupivacain and magnesium sulfate injection (LM group). Patients were compared with postoperative VAS (Visual Analog Score) score during rest and activity, opioid analgesic need, non-opioid analgesic need and other medication needs. Results: Postoperative VAS scores during rest and activation at early postoperative period were significantly lower at LM group when compared with L group and lower than control group at all time periods. Opioid analgesic need, non-opioid analgesic need and other medication needs for non-pain symptoms were lower at LM group when compared with L and control groups at all time periods. Conclusion: Intraarticular magnesium sulfate plus Levobupivacain injection is a safe and effective method for post operative pain management after arthroscopic meniscectomy.Keywords: Intra-articular injection, Magnesium sulfate, Levobupivacain, Postoperative analgesia, Chondrocyte apoptosis, Pain management, Arthroscopic menisectomy Level of Evidence: Level I, Therapeutic study Keywords: Intra-articular injection, Magnesium sulfate, Levobupivacain, Postoperative analgesia, Chondrocyte apoptosis, Pain management, Arthroscopic menisectomy